Creative criticism - "Weisinger, Hendrie" (London, 1989)
Giving and taking criticism can be the most difficult and stressful parts of the job - yet success at work demands that you do both, often and well. Whether you manage, sell, negotiate, supervise or collaborate, criticism comes with your job: it must be skilfully received and expressed if you are to stay on track professionally. It shows how to transform the necessary exchange of criticism - be it between you and your boss, your peers, or your subordinates - from a destructive, demoralizing encounter into a positive, motivating, mutually beneficial experience. Written by a psychologist, this book demonstrates specific techniques and strategies for applying criticism up and down the corporate ladder. It shows how to conduct performance appraisals so that they stimulate better performance and how executives and managers can solicit valid criticism from their subordinates and thus ensure that the best decisions are always made. Finally, the author explains how to use these skills within the most difficult and common situations, including such daunting encounters as criticizing clients and customers. Using true-to-life examples, the author illustrates how to use criticism as a powerful tool, one that will help you to improve your skills, enhance your working relationships, increase your job satisfaction and achieve better overall results. Dr Hendrie Weisinger also wrote "Wall Street Journal", "Nobody's Perfect", "Dr Weisinger Anger Work-Out Book".
Keywords: "Psychology, Applied"